PENERAPAN TEORI BEHAVIORISTIK TERHADAP MOTIVASI BELAJAR SISWA MENGGUNAKAN MEDIA PEMBELAJARAN - Yustina, Armi; Muti'ah, Titik (Jurnal Pendidikan Dasar Flobamorata, 2023)
The world of education continues to change along with the development of technology and informatics. Changes have positive and negative impacts on the world of education. Currently school-age children enter the Z generation (2001-2010). Generation Z children are used to using technology and cannot be separated from smartphones and social media. The characteristic of Generation Z is that learning must be concise, practical and visual. The use of mobile phones for learning media can be one of the innovations in learning. The existence of a stimulus from learning media gives a positive response in the form of student learning motivation. This is in line with behavioristic theory which focuses on student behavior. The research objective is the application of behavioristic theory to students' learning motivation using learning media. The method used is a qualitative description using research instruments in the form of interviews, questionnaires. The subjects of this study were class VI students who would take their final school exams at Kiyaran 2 Public Elementary School. The results of this study were an increase in students' learning motivation by using learning media. From the initial conditions the average student motivation of 67 increased to 77 in cycle I and 85 in cycle II.